We are given this quadratic equation :
![f(x) =-x^(2) -6x](https://img.qammunity.org/2019/formulas/mathematics/middle-school/j3fs5mp7e8p0fqc3h17c4svs17uacryuqz.png)
For a given equation of the form:
![f(x) =ax^(2) +bx +c](https://img.qammunity.org/2019/formulas/mathematics/middle-school/bm7h87pc6uf2rw4u3budcg6fhke9uz33o2.png)
We can find the vertex (h,k), by first finding h of vertex by :
............(1)
and k(y-coordinate) can be found by plugging this x-value in the given equation.
Now if we compare our equation with the general form, we can find our a, b and c as :
a=-1 and b=-6 and c=0
so plugging these values in equation (1), to get x-coordinate as
![h=-(b)/(2a) = -(-6)/(2*(-1))](https://img.qammunity.org/2019/formulas/mathematics/middle-school/jtoa7we4dzwpnhvkft04lu1vu2dwuuo51b.png)
![h=-(-6)/(-2) = -(6)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/d71d8kwkjq6k97t3u87an5vhvrv2jvticw.png)
h=-3
Now plugging this value in the given equation to solve for x,
![f(x) = -((-3)^(2) ) -6(-3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/75djnl6tgyycp48rw7so6pextf8beclocz.png)
![f(x) = -(9) -6(-3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/nwpyrvr99wj77r05xpisixi297sz9ugspg.png)
![f(x) = -9 +18](https://img.qammunity.org/2019/formulas/mathematics/middle-school/5cwh3fizgtkb9o93wg9sochipqdswdsqb2.png)
![f(x) = 9](https://img.qammunity.org/2019/formulas/mathematics/middle-school/mp01i38qao6eojg458xa2qg66zhg47l4h9.png)
k=9
So vertex is (-3,9)